NGR-hTNF in combination with best investigator choice in previously treated malignant pleural mesothelioma (NGR015): a randomised, double-blind, placebo-controlled phase 3 trial. Issue 6 (June 2018) - Gregorc, Vanesa; Gaafar, Rabab M; Favaretto, Adolfo; Grossi, Francesco; Jassem, Jacek; Polychronis, Andreas; Bidoli, Paolo; Tiseo, Marcello; Shah, Riyaz; Taylor, Paul; Novello, Silvia; Muzio, Alberto; et al.
Summary: Background: Malignant pleural mesothelioma is an aggressive cancer with highly vascularised tumours. It has poor prognosis and few treatment options after failure of first-line chemotherapy. NGR-hTNF is a vascular-targeting drug that increases penetration of intratumoral chemotherapy and T-cell infiltration by modifying the tumour microenvironment. In this trial, we aimed to investigate the efficacy and safety of NGR-hTNF in patients with malignant pleural mesothelioma who had progressed during or after a first-line treatment. Methods: NGR015 was a randomised, double-blind, placebo-controlled phase 3 trial done in 41 centres in 12 countries. Eligible participants had malignant pleural mesothelioma of any histological subtype (epithelial, sarcomatoid, or mixed), were aged 18 years or older, and had an Eastern Cooperative Oncology Group performance status of 0–2 and radiologically documented progressive disease after one pemetrexed-based chemotherapy regimen. Participants were randomly assigned to receive weekly NGR-hTNF 0·8 μg/m 2 intravenously plus best investigator choice (n=200), or placebo plus best investigator choice (n=200). Best investigator choice was decided before random assignment and could be single-agent gemcitabine (1000–1250 mg/m 2 intravenously), vinorelbine (25 mg/m 2 intravenously or 60 mg/m 2 orally), doxorubicin (60–75 mg/m 2 intravenously), or best supportive care only. Patients were randomised (1:1) with a block size of four after stratification for performance status and best investigator choice. The primary study endpoint was overall survival in the intention-to-treat population. The trial is closed to new participants and is registered withClinicalTrials.gov (NCT01098266 ). Findings: Between April 12, 2010 and Jan 21, 2013, we enrolled 400 eligible participants. 381 (95%) of 400 patients were selected to receive chemotherapy before all participants were randomly assigned to receive NGF-hTNF plus best investigator choice (n=200) or placebo plus best investigator choice (n=200). At the cutoff date (April 29, 2014), the median follow-up was 18·7 months (IQR 15·1–24·4), and overall survival did not differ between the two treatment groups (median 8·5 months [95% CI 7·2–9·9] in the NGR-hTNF group vs 8·0 months [6·6–8·9] in the placebo group; hazard ratio 0·94, 95% CI 0·75–1·18; p=0·58). Grade 3 or worse study-emergent adverse events occurred in 136 (70%) of patients receiving NGR-hTNF versus 118 (61%) of patients receiving placebo, with the most common being neutropenia (35 [18%] of 193 patients vs 36 [19%] of 193 patients), pain (11 [6%] vs 16 [8%]), dyspnoea (nine [5%] vs seven [4%]), and chills (nine [5%] vs none). 50 (26%) patients in the NGR-hTNF group had a serious adverse event, compared with 47 (24%) in the placebo group. Treatment-related serious adverse events occurred in 17 (9%) patients in the NGR-hTNF group and 20 patients (10%) in the placebo group. There were 12 deaths in the NGR-hTNF group and 13 deaths in the placebo group, but none were treatment related. Interpretation: The study did not meet its primary endpoint. The hypothesis-generating findings from the subgroup analyses deserve a confirmatory randomised trial because patients who rapidly progress after first-line treatment have a poor prognosis. Funding: MolMed.